CAFs orchestrates tumor immune microenvironment—A new target in cancer therapy? - Zhang, Chunxue; Fei, Yuxiang; Wang, Hui; Hu, Sheng; Liu, Chao; Hu, Rong; Du, Qianming (Frontiers in Pharmacology, 2023)
As the primary constituent of tumor microenvironment (TME), Cancer-associated fibroblasts (CAFs）are a heterogeneous group and the predominant extracellular stromal component of tumor cells with the ability to secrete a variety of cytokines that regulate tumor cell development. It has been demonstrated that tumor formation is based not only on the high clonal proliferation potential of tumor cells, but also on their TME. The interaction of CAF with tumor-infiltrating immune cells and other immunological components generates immunosuppressive TME, which aids in the evasion of immune surveillance by cancer cells. This review describes the mechanism underlying the mediation of CAFs on tumor progression, as well as CAFs interact with immune cells in the microenvironment. Special emphasis is put on how they work together to help tumors grow and hide from the immune system.